Misconceptions on COVID-19 Risk Among Ugandan Men: Results From a Rapid Exploratory Survey, April 2020 - Kasozi, Keneth Iceland; MacLeod, Ewan; Ssempijja, Fred; Mahero, Michael W.; Matama, Kevin; Musoke, Grace Henry; Bardosh, Kevin; Ssebuufu, Robinson; Wakoko-Studstil, Florence; Echoru, Isaac; Ayikobua, Emmanuel Tiyo; Mujinya, Regan; et al. (Frontiers in Public Health, 2020)
Background The aim of the study was to identify possible misconceptions among males and females towards COVID-19 in Uganda using a rapid online survey distributed via social media. Methods A cross-sectional survey carried out during 9th - 16th April 2020 was conducted amongst Ugandans, and only 161 Ugandan purposively participated in the online questionnaire that assessed the respondents understanding of the risks and outcome of infection with COVID-19 among males and females. Results We found significant divergences of opinion on gendered susceptibility to COVID-19. Most female respondents considered infection risk, symptoms, severe signs and death to be equally distributed between genders. In contrast, male respondents believed they were more at risk of infection, severe symptoms, severe signs and death (52.7% vs. 30.6%, RR = 1.79, 95% CI: 1.14-2.8). Most women did not share this perception and disagreed that males were at higher risk of infection (by a factor of three), symptoms (79% disagree), severe signs (71%, disagree) and death (70.2% disagree). Overall, most respondents considered children less vulnerable (OR = 1.12, 95% CI: 0.55-2.2) to COVID-19 than adults, that children present with less symptoms (OR = 1.57, 95% CI: 0.77-3.19) and there would be less mortality in children (OR = 0.92, 95% CI: 0.41-1.88). Of female respondents, 76.4% considered mortality from COVID-19 to be different between the young and the elderly (RR = 1.7, 95% CI: 1.01-2.92) and 92.7% believed young adults would show fewer signs than the elderly and 71.4% agreed that elderly COVID-19 patients would show more severe signs than the young (OR = 2.2, 95%CI: 1.4, 4.8). Conclusion WHO has identified women and children in rural communities as vulnerable persons who should be given more attention in the COVID-19 national response programs across Africa; however, our study has found that men in Uganda perceive themselves to be at greater risk and that these contradictory perceptions (including the association of COVID-19 with “the White” race) suggest an important discrepancy in the communication of who is most vulnerable and why.